The Effect of Air Velocity Variations on the Fire Characteristics and Water Heating Time in Used Oil-Fired Multifuel Stoves - Muhammad Satya Putra Gantada; Yudi Setiawan; Saparin Saparin; Eka Sari Wijianti (Interdisciplinary Social Studies, 2025)
One of the uses of used oil is as fuel for multifuel stoves. A multifuel stove is a stove that has flexibility in its fuel selection. In the operation of a multifuel stove, the air supply plays an important role in the combustion process. This study discusses the influence of air velocity on fire characteristics and water temperature during the heating process. In this study, three variations of air velocity were used, namely 13 m/s, 12 m/s, and 11 m/s. Based on the tests that have been carried out, it was found that the speed of air blown into the combustion chamber can affect the temperature and duration of the flame. The faster the speed of air that is blown into the combustion chamber, the higher the temperature of the flame will be, but the faster the fire will be extinguished. This is because more oxygen is supplied into the combustion chamber, causing the combustion process to take place more quickly and intensely. Meanwhile, regarding the water heating time, the time required by the three variations of air speed to heat 0.5 kg of water to boiling is 1.5–2 minutes, which surpasses the performance of gas stoves and conventional electric stoves.